Difficulties in management of patients with systemic lupus erythematosus and antiphospholipid syndrome in combination with melanoma and infiltrative tuberculosis (clinical observations) - A. A. Shumilova; T. M. Reshetnyak; F. A. Cheldieva; A. M. Lila (Современная ревматология)
We present two clinical cases: the first patient had combination of antiphospholipid syndrome (APS) and melanoma, and the second – systemic lupus erythematosus (SLE) and APS, melanoma, infiltrative tuberculosis and Herpes zoster. Managing patients with SLE combined with APS is really challenging. Infections and malignant neoplasms, along with kidney damage and cardiovascular diseases, are a significant cause of death in this cohort of patients. The role of antibodies to phospholipids in the onset of malignancy is still under discussion. The combination of rheumatic diseases with oncological or infectious pathology complicates therapy, limiting the use of drugs, recommended by clinical guidelines.